Mycoplasma pneumoniae infections in school children of a tropical community - Campos, E (1993)
Information about Mycoplasma pneumoniae infections in tropical countries is scarce. This study reporta the prevalence oF anti-M. pneumoniae antibodies among school children from the tropical community of Palmares, Costa Rica. The serum samples were collected in July 1983 Crom 2021 children who represented 99% of the county' s schoolchildren. Immunofluorescense (lPA) and in some cases EUSA serological methods were applied. IFA seropositivity was high (53%) and ranged from 22% to 79% depending on the distriCL Marked differences in the prevalence of antibodies in children attending schools of neighboring communities. suggest that the school may be epidemiologícally important as a focus to spread mycoplasma infections among children. the presence of a low percentage of antibodies (lgG, IgM and IgA) against the 168 kd- M. pneumoniae antigen suggested that there were few cases of active or recent infections.